Artificial intelligence in virtual teaching and learning environments: A model proposal (Research, Society and Development, 2021)
Among the technologies that impact contemporary life, Artificial Intelligence (AI) stands out for its influence on social and production relations in various areas, such as finance, retail, mobility, health and education. Among these, the Learning Management System (LMS) deserve to be highlighted, they are used as didactic and technological tools, characterized by incorporating technologies throughout their history. This article aimed to propose a virtual teaching and learning environment model from the creation of intelligent agents that will act as support and sensors for the teaching and learning stages. Contributing to advance the solution of the question: how can Artificial Intelligence techniques, when incorporated into LMS, add value in the teaching and learning process by increasing the interaction between agents? Qualified as a qualitative study, oriented to phenomenological processes with exploratory objective using documentary techniques, the research followed a methodological path considering the realization of literature review that contributed to the construction of the state of the art, followed by the application of research techniques, collection and analysis of data that contributed to support the construction of the proposed model and subsequent validation with specialists. In the end, it was possible to structure the LMS model with AI techniques that can add value to teaching and learning relationships, paving the way for the expansion of the discussion with the scientific community, as well as serving as a reference for possible materialization of the proposal.